Shuffling pathway of anti-twinning in body-centered-cubic metals. (1st January 2023) - Xie, Hongxian; Wei, Gaobing; Du, Jun-Ping; Ishii, Akio; Lu, Guanghong; Yu, Peijun; Ogata, Shigenobu
Abstract: In this study, anti-twinning and deformation twinning of body-centered-cubic (BCC) metals under shear loading in the anti-twin direction were examined. Molecular dynamics simulations of BCC Ta showed both the existence of anti-twinning and a novel two-layer-by-two-layer anti-twinning mechanism consisting of a staggered shuffle sliding of { 112 } atomic planes in the [ 11 1 ¯ ] and [ 1 ¯ 1 ¯ 1 ] directions, generating finite shear displacement along the anti-twin direction. The density functional theory multi-dimensional interlayer slipping energy landscape of the newly observed anti-twinning process has a lower energy barrier for both twin nucleation and growth than the recently proposed layer-by-layer anti-twinning process. Graphical abstract: Image, graphical abstract